Pemodelan Farmakokinetika Berbasis Populasi dengan R: Model Dua Kompartemen Ekstravaskuler: Population-Based Pharmacokinetics Modeling with R: Two Compartment Extravascular Model - Notario, Dion (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2018)
A Tutorial of two-compartment extravascular population-based pharmacokinetics modeling was performed by differential equations and non-linear mixed effect model approach. First, three-level differential equations of two-compartment pharmacokinetics were generated. Then, covariate and non-covariate models were developed by nlmeODE and nlme packages installed in R. The best model was selected according to AIC, BIC, and LogLik value. A model without covariates model was selected as the best model. The selected model showed a goodness of fit with experimental dataset and residual plot of the model revealed that no violations of model assumtions. In conclusion, nlme and nlmeODE is capable to generate an adequate predictive model of two-compartment population-based pharmacokinetics for extravascular route